Structural and spectroscopic evidence of strong electronic delocalization through a cyanido bridge in a mixed-valence Os-Ru complex - Rossi, Melina Brenda (2010)
We report the properties of a trinuclear cyanido-bridged complex, trans-(dmap)4RuII(Âμ-NC)OsIII(CN) 524- [14-; dmap = 4-(dimethylamino)pyridine], whose structure and electronic and vibrational spectra present strong evidence of partial redox states for the three metal ions, an unprecedented feature for cyanido-bridged systems. Matching the energy of metal fragments bonded by a cyanido bridge results in asystem that is better described as having partial RuII/III and OsII/ III character as evidenced by its structure and its spectroscopic analysis.